Comparison of Hand Muscle Strength, Arm Muscle Strength, Back Muscle Strength, Abdominal Muscle Strength, and Flexibility among Calisthenics Communities in Yogyakarta - Isnanto, Juni (Edumaspul: Jurnal Pendidikan, 2025)
This research aims to find scientifically accurate answers about whether there are differences in the level of hand muscle strength, arm muscle strength, back muscle strength, abdominal muscle strength, and flexibility among the calistheninics communities such as Aldebaran YSW and Sambilegi Fit.This reserch was a comparative study using a survey method. The research subjects were 9 members of the Aldebaran YSW calisthenics community and 11 members of the Sambilegi Fit Yogyakarta Calisthenics Community who were active in calisthenics. The data collection used 5 test items, for the hand muscle strength test with handgrip dynamometer, arm muscle strength test with 30 second push-ups test, back muscle strength test with back dynamometer test, abdominal strength test with 30 second sit-ups test, flexibility test with sit and reach test. The data analysis used t-test analysis through the prerequisite test for normality and homogeneity tests. The result of this study indicate that: there is a significant difference in hand muscle strength with an average difference of 7.19% for the right hand and 8.18% for the left hand, the arm muscle strength with a difference from the average of 12.61%, back muscle strength with an average difference of 16% between the Aldebaran YSW and Sambilegi Fit calisthenics community. It is indicated by the value of t-count > t-table and sig value < 0.05. There is no significant difference in abdominal muscle strength and flexibility between Aldebaran YSW and Sambilegi Fit calisthenics community with an average difference of 1.98% in abdominal muscle strength and 6.64% in flexibility. .